2017
DOI: 10.1073/pnas.1704786114
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic-site design for inverse heavy-enzyme isotope effects in human purine nucleoside phosphorylase

Abstract: Heavy-enzyme isotope effects ( 15 N-, 13 C-, and 2 H-labeled protein) explore mass-dependent vibrational modes linked to catalysis. Transition path-sampling (TPS) calculations have predicted femtosecond dynamic coupling at the catalytic site of human purine nucleoside phosphorylase (PNP). Coupling is observed in heavy PNPs, where slowed barrier crossing caused a normal heavyenzyme isotope effect (k chem light /k chem heavy > 1.0). We used TPS to design mutant F159Y PNP, predicted to improve barrier crossing fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
45
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(45 citation statements)
references
References 39 publications
0
45
0
Order By: Relevance
“…Strategies previously employed in the literature by various groups include isotopically labelling the entire enzyme or labelling either of single amino acid residues or of particular segments, such as mobile loops (Figure ) . The effects of protein isotope labelling on transition states have been characterised in different enzymes including purine nucleotide phosphorylase (PNP), HIV protease (HIV‐1 PR), alanine racemase, dihydrofolate reductase (DHFR), pentaerythritol tetranitrate reductase (PETNR), formate dehydrogenase (FDH), lactate dehydrogenase (LDH) and alcohol dehydrogenase . In most of these cases, isotope labelling reduced the rate of the chemical step .…”
Section: Heavy Enzymesmentioning
confidence: 99%
See 2 more Smart Citations
“…Strategies previously employed in the literature by various groups include isotopically labelling the entire enzyme or labelling either of single amino acid residues or of particular segments, such as mobile loops (Figure ) . The effects of protein isotope labelling on transition states have been characterised in different enzymes including purine nucleotide phosphorylase (PNP), HIV protease (HIV‐1 PR), alanine racemase, dihydrofolate reductase (DHFR), pentaerythritol tetranitrate reductase (PETNR), formate dehydrogenase (FDH), lactate dehydrogenase (LDH) and alcohol dehydrogenase . In most of these cases, isotope labelling reduced the rate of the chemical step .…”
Section: Heavy Enzymesmentioning
confidence: 99%
“…Theoreticians have proposed that introducing a new “promoting motion” would improve the activity of aromatic amine dehydrogenase but this has never been tested experimentally . Similarly, work on PNP has shown that the efficiency of barrier crossing in a heavy enzyme can be modified by mutations that enhance promoting vibrations . Experimentally, this resulted in the inversion of the enzyme KIE from a normal KIE of 1.31 to an inverse KIE of 0.75 .…”
Section: Future Outlook For Protein Engineeringmentioning
confidence: 99%
See 1 more Smart Citation
“…Few reports have indicated that heavy enzymes can have faster chemistry than the light counterpart. With PNP, TPS explored the possibility that a mass-altered catalytic site mutant protein could be designed to exhibit increased chemistry rates relative to its unlabeled counterpart at the catalytic site (19). The analysis indicated that altering phenylalanine 159 to tyrosine (F159Y) would create an enzyme where the femtosecond dynamics of the heavy enzyme were more likely to find the transition state than the same enzyme in its natural isotopic form.…”
mentioning
confidence: 99%
“…This protein design element from TPS was confirmed by demonstrating a k chem light / k chem heavy of 0.75. However, the F159Y mutation in PNP also caused less efficient catalytic site chemistry, slowing it by a factor of 32 (19). An inverse heavy-enzyme isotope effect was also Significance Enzymes achieve catalytic efficiency by optimizing contacts between reactants and catalytic site amino acids.…”
mentioning
confidence: 99%